1997
DOI: 10.1038/sj.pcan.4500209
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of vasectomy, time since vasectomy and prostate cancer

Abstract: Past studies of the association of vasectomy and prostate cancer have reported inconsistent results. Our objective was to investigate whether vasectomy and time since vasectomy are associated with a higher risk of prostate cancer. We conducted a cross-sectional study on unduplicated records of b 95 000 participants in a longitudinal study (1993±1995) of prostate cancer screening conducted during Prostate Cancer Awareness Week. Vasectomy was reported by 28%, and there were 2530 biopsies. w 2 tests and logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…After screening the abstracts or titles, most of them were excluded, because they were case-control studies, letters and reviews, or the exposure and endpoint were not linked to our study or they were duplicate publications. After that, 10 cohort studies involving more than 7027 cases and 429914 participants were included 5 6 8 13 14 15 16 19 20 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening the abstracts or titles, most of them were excluded, because they were case-control studies, letters and reviews, or the exposure and endpoint were not linked to our study or they were duplicate publications. After that, 10 cohort studies involving more than 7027 cases and 429914 participants were included 5 6 8 13 14 15 16 19 20 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The publication years of them ranged 1991 to 2014. Of them, 6 were conducted among American males 5 8 13 14 16 19 , 1 in England 20 and Brazil 15 , 2 in Denmark 6 21 , respectively. 2 studies were based on all years old populations 6 19 , 6 studies were conducted among the middle-aged and elderly populations 5 8 14 15 16 20 , but the other 2 studies did not report this 13 21 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results suggested a slightly increased risk of prostate cancer in men who had had a vasectomy; however, the data were not statistically significant, and the relationship was determined to be noncausal. The same year, DeAntoni et al 46 performed a large cohort study that ultimately found no association between prostate cancer and vasectomy. These results were supported by a study of Lesko et al 47 in 1999, who performed a case–control study that reported no correlation at all between prostate cancer and vasectomy.…”
Section: History Of Original Articles Discussing Prostate Cancer and mentioning
confidence: 99%